2004
DOI: 10.1002/fld.683
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of the rotating viscous flow approaching a solid sphere

Abstract: SUMMARYA numerical simulation is performed to investigate the ow induced by a sphere moving along the axis of a rotating cylindrical container ÿlled with the viscous uid. Three-dimensional incompressible Navier-Stokes equations are solved using a ÿnite element method. The objective of this study is to examine the feature of waves generated by the Coriolis force at moderate Rossby numbers and that to what extent the Taylor-Proudman theorem is valid for the viscous rotating ow at small Rossby number and large Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…The present results are in quite good agreement with those experimental and numerical data. Further, the present computational code has also been verified in our previous study (Lu et al, 2002;Wang et al, 2004).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…The present results are in quite good agreement with those experimental and numerical data. Further, the present computational code has also been verified in our previous study (Lu et al, 2002;Wang et al, 2004).…”
Section: Resultssupporting
confidence: 65%
“…A time-accurate finite element method based on a fractional-step velocity correction (Kovacs and Kawahara, 1991;Lu et al, 2002;Chen and Lu, 2004;Wang et al, 2004) is applied to solve Eqs. (1) and (2).…”
Section: Methodsmentioning
confidence: 99%
“…Perhaps not surprisingly, this regime turns out to correspond to that in which inertial waves can propagate through the fluid. That is to say, it is observed that inertial waves can propagate in a quasi-linear manner through a still fluid (still in the rotating frame) whenever is less than , but nonlinear effects become very evident in the range and indeed no waves are observed whenever exceeds a value of around (Maxworthy 1970, Wang, Lu & Zhuang 2004, Sreenivasan & Davidson 2008). Of course, the exact value of at which waves cease to propagate depends on the precise definitions of and .…”
Section: The Role Of Inertial Waves In Columnar Vortex Formationmentioning
confidence: 99%
“…Many numerical studies of single-particle dynamics in rotating flows have been concerned with the motion of a particle in a fluid-filled cylinder rotating about a vertical axis (Minkov, Ungarish & Israeli 2000Wang, Lu & Zhuang 2004). Fewer studies exist on the single-particle dynamics in a fluid-filled cylinder rotating about a horizontal axis (see figure 1), (see for example, Annamalai & Cole 1986;Roberts, Kornfeld & Fowlis 1991;Gao et al 1997;Coimbra & Kobayashi 2002;Lee & Ladd 2002;Ramirez et al 2004).…”
Section: Introductionmentioning
confidence: 99%